(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the development of the "Integrated Strategy" method, which has an innovative character in improving the system of organization and management of technological education processes, the use of demonstration and reorganization approaches for the first time, as well as four stages of effective organization of technological education processes (organizational, propaedeutic, basic and the final stages) and the presence of three main conditions (strengthening students’ thinking, objectivity of the thinking process and determining the solution to educational problems) process was studied.